2023
DOI: 10.3390/min13081044
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Regularity of Carboniferous Weathered Black Shale in Qiziqiao Area, Central Hunan

Abstract: The Hunan region is a high geological background area of black rock series rich in various metallic elements; accordingly, local heavy metal pollution is severe. Previous studies on black shale have primarily focused on the lower Cambrian strata, while research on Carboniferous black shale remains scarce. To better explore the activity law of heavy metals during Carboniferous black shale weathering, this study analyzed the elemental components of samples through field observations of outcrops in the Qiziqiao a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…After exposure, it decomposes easily via weathering, producing acidic drainage. Driven by hydrodynamic forces, it can accelerate the migration of heavy metals to surrounding and downstream farmland soils, which further threatens the ecological environment and human health [44][45][46].…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…After exposure, it decomposes easily via weathering, producing acidic drainage. Driven by hydrodynamic forces, it can accelerate the migration of heavy metals to surrounding and downstream farmland soils, which further threatens the ecological environment and human health [44][45][46].…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…The major lithologies of the Permian Dalong Formation are black siliceous shale, calcareous shale, and siliceous limestone. Black rock series are regarded as the primary geological sources of Se enrichment on Earth, and they are rich in OM [59][60][61][62][63]. The background values for Se in black rock series have not been published; however, Wang et al reported that the mean content of Se in Chinese coal is as high as 3.91 mg/kg [64].…”
Section: Relationship Of Soil Type With Se Contents In Topsoilmentioning
confidence: 99%